A Case Study of Production Line Balancing With Simulation - Intan Bazliah, Mohd; Abdullah, Ibrahim (Penerbit Universiti Malaysia Pahang, 2016)
The purpose of this paper is to simulate production line improvement using computerized simulation software. The model is developed based on current state operation system which had been identified to have imbalanced performance between 18 workstations. The paper presents the analysis of simulation model to overcome the stated problems. The findings found that by having balance production system in assembly line will be able to optimize overtime and job performance while eliminating a number of buffer stock (work in progress). The results also encourage the multi-tasking and job rotation which can promote job optimization.